Estrada-parque: proposta para uma definição - Soriano, Afranio José Soares [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
As áreas protegidas são implantadas com diferentes níveis de restrição quanto ao uso direto ou indireto dos recursos naturais e sócio-culturais por meio de categorias de manejo respaldadas na lei e por princípios técnico-científicos. Porém as estradasparque, no Brasil, não seguem a essa regra por não possuírem definição e normatização adequadas. Esta indefinição coloca em risco não somente a conservação da biodiversidade como possibilita a manipulação das políticas ambientais pelos mais diferentes grupos de interesse, por justificar a construção irresponsável de estradas em áreas que dificilmente, devido a questão ambiental, seriam autorizadas. Com o intuito de reverter essa situação foi elaborada uma definição para estrada-parque enquanto uma unidade de conservação com base nos conceitos de desenvolvimento sustentável, paisagem, percepção ambiental e na opinião de pesquisadores, técnicos e gestores ambientais por meio de questionário. Também foi proposto uma classificação tipológica com quatro tipos básicos: estradaparque; estrada ecológica; estrada eco-turistica ou turística e estrada cênica.

The protecting areas are implanted with different levels of restriction in regards to the direct or indirect use of the natural resources and socio-cultural by means of endorsed categories of handling in the law and for technician-scientific principles. However the roads-park, in Brazil, don t follow this rule for haven t an adequate definition and standardization. The fact is that roads parks nor always cause great impact, and although it can come to be an important instrument of conservation and sustainable development, it can also serve of instrument of manipulation for power groups, interested only in promoting the implantation of roads, in protecting areas, or the another way, it hardly would be established. With intention to revert this situation the definition for road-park was elaborated while an unit of conservation on the basis of the concepts of sustainable development, landscape, environmental perception and in the opinion of researchers, environmental technician and managers by means of questionnaire. Also the classification with four basic types was considered: roadpark; ecological road; tourist road or echo-tourist road and scenic road. This classification could be defined after the characterization of the 24 existing roads in Brazil, by means of interviews, bibliographical research and techniques visits, that included the Blue Ridge Parkway, the first road-park of the world, with the aim to know the model American.
Keywords: Ecologia; Politicas publicas; Política ambiental; Unidades de conservação; Estradas-parque; Protected areas; Parkways; Public policies of environment; Management; Landscape